Clipped wings : the rise and fall of the Women Airforce Service Pilots (WASPs) of World War II - Merryman, Molly (New York University Press, 2020)
Molly Merryman draws upon military documents--many of which weren't declassified until the 1990s--congressional records, and interviews with the women who served as WASPs during World War II to trace the history of the over one thousand pilots who served their country as the first women to fly military planes. She examines the social pressures that culminated in their disbandment in 1944--even though a wartime need for their services still existed--and documents their struggles and eventual success, in 1977, to gain military status and receive veterans' benefits.In the preface to this reissued edition, Merryman reflects on the changes in women's aviation in the past twenty years, as NASA's new Artemis program promises to land the first female astronaut on the moon and African American and lesbian women are among the newest pilot recruits. Updating the story of the WASPs, Merryman reveals that even in the past few years there have been more battles for them to fight and more national recognition for them to receive. At its heart, the story of the Women Airforce Service Pilots is not about war or planes; it is a story about persistence and extraordinary achievement. These accomplished women pilots did more than break the barriers of flight; they established a model for equality.